The Training on Making Pinnate Leaves Cakes toward Housewives of Lahai Roi Congregation, Tofa: Pelatihan Pembuatan Kue Basah Kelor bagi Kaum Ibu Jema’at Lahai Roi-Tofa - Naat, Johnson N.; Lawa, Yosep; Neolaka, Yantus A. B.; Lestarani, Dewi; Parera, Lolita A. M.; Liunokas, Yanpitherzon (Mattawang: Jurnal Pengabdian Masyarakat, 2021)
Marunggai tree leaves tree is a special plant in East Nusa Tenggara province with its high nutrient. It grows mostly in the house environment of the congregation of Lahai Roi church, Tofa and it is manufactured only as a kind of vegetable that makes consumers are less interested, but if it is manufactured in different kinds of meals its consumption can get increased. The less understanding in manufacturing marunggai leaves may emerge undelicious smell. This writing is a public service one that is important to train all housewives in Lahai Roi congregation, Tofa to make pinnate leaves wet cakes. The methods used were discussion and training methods of making pinnate leaves wet cakes (like cake, brownie, and tiramisu cakes). The result shows that the percentages of those housewives understanding in making pinnate leaves cakes, such as cake, brownies, and tiramisu cakes are in orderly 97%, 95.2%, and 91.7%. These percentages indicate that the housewives in Lahai Roi congregation, Tofa have a good understanding and they can make pinnate leaves wet cakes. By conducting the training of making pinnate leaves wet cakes in Lahai Roi congregation, Tofa it can increase community interest in consuming pinnate leaves that have high nutrients. Abstrak Tanaman kelor merupakan salah satu tanaman khas NTT yang mempunyai nilai gizi tinggi. Tanaman ini banyak tumbuh dipekarangan jemaat Lahai Roi Tofa dan hanya diolah menjadi sayuransehingga kurang diminati namun jika diolah menjadi jenis makanan yang berbeda dan inovatif akan meningkatkan konsumsi kelor. Kurangnya pemahaman dalam mengolah daun kelor akan menghasilkan bau yang kurang sedap. Pengabdian ini penting untuk melatih kaum ibu jemaat Lahai Roi Tofa dalam membuat kue basah kelor. Metode yang digunakan dalam pengabdian ini adalahdiskusi dan pelatihanpembuatan kue basah kelor (cake, brownis dan tiramisu). Hasil pengabdian menunjukkan persentasi pemahaman kaum ibu dalam pembuatan kue cake, brownis dan tiramisukelor berturut-turut adalah 97%, 95,2% dan 91,7%. Hal ini menunjukkan bahwa kaum ibu jemaat Lahai Roi mampu dan memahami pembuatan kue basah kelor. Adanya pelatihan pembuatan kue basah berbahan kelor di jemaat Lahai Roi Tofa dapat meningkatkan minat masyarakat dalam mengkonsumsi daun kelor yang memiliki nilai gizi tinggi.